2010
DOI: 10.1007/s11357-010-9153-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality and metabolic syndrome

Abstract: The prevalence of metabolic syndrome has paralleled the sharp increase in obesity. Given its tremendous physical, emotional, and financial burden, it is of critical importance to identify who is most at risk and the potential points of intervention. Psychological traits, in addition to physiological and social risk factors, may contribute to metabolic syndrome. The objective of the present research is to test whether personality traits are associated with metabolic syndrome in a large community sample. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 34 publications
(31 reference statements)
5
87
3
2
Order By: Relevance
“…However, previous studies (see also Dishman et al, 2008) have shown that human personality is related to healthrelated behaviours (e.g. exercise and maintaining a good diet) (Booth-Kewley and Vickers, 1994), obesity (Lykouras, 2008;Barry et al, 2009), and the metabolic syndrome (Sutin et al, 2010). Donahoo et al (Donahoo et al, 2004) and Johanssen and Ravussin (Johanssen and Ravussin, 2008) speculated that individuals with inherently higher SPA may subconsciously tend to choose jobs that are more physically demanding.…”
Section: Personality Correlates Of Physical Activitymentioning
confidence: 99%
“…However, previous studies (see also Dishman et al, 2008) have shown that human personality is related to healthrelated behaviours (e.g. exercise and maintaining a good diet) (Booth-Kewley and Vickers, 1994), obesity (Lykouras, 2008;Barry et al, 2009), and the metabolic syndrome (Sutin et al, 2010). Donahoo et al (Donahoo et al, 2004) and Johanssen and Ravussin (Johanssen and Ravussin, 2008) speculated that individuals with inherently higher SPA may subconsciously tend to choose jobs that are more physically demanding.…”
Section: Personality Correlates Of Physical Activitymentioning
confidence: 99%
“…Other personality traits, such as low agreeableness and interpersonal hostility, have also been associated with morbidity (Sutin et al, 2010), although less consistently (Deary et al, 2010;Smith & MacKenzie, 2006;Sutin et al, 2010). Personality might also influence the risk of adult diabetes, via behavior-related risk factors, such as physical activity and obesity (Jokela et al, 2013).…”
mentioning
confidence: 99%
“…Based on earlier studies examining related health outcomes (Jokela et al, 2013;Sutin et al, 2010), we hypothesized that low conscientiousness, high neuroticism, and low agreeableness are associated with higher risk of incident diabetes and diabetesrelated mortality.…”
mentioning
confidence: 99%
“…Although men tend to score slightly higher in antagonism than women, the correlates of antagonism generally do not differ by sex. For example, the association between antagonism and aggressive behavior is similar for men and women (Seibert, Miller, Pryor, Reidy, & Zeichner, 2010), as is the association between antagonism and risk of metabolic syndrome (Sutin et al, 2010). Further, the association between antagonism-related traits and smoking initiation does not differ by sex (Welch & Poulton, 2009).…”
mentioning
confidence: 90%